Fractal Dimension of the EEG for Detection of Behavioural Microsleeps - Peiris, M.T.R.; Jones, R.D.; Davidson, P.R.; Bones, P.J.; Myall, D.J. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2005)
The fractal dimension (FD) of EEG has been shown to be of value in the detection of epileptic seizures. In this paper, we assess its usefulness in detecting behavioural microsleeps. Fifteen non-sleep-deprived normal subjects performed two 1-hour sessions of a continuous tracking task while EEG, EOG and facial video were recorded. Higuchi's algorithm was used to calculate the FD of the EEG. Video lapses were scored independently from tracking performance by a human rater. A subset of data was rated independently by three human raters observing both tracking performance and the video rating to identify behavioural microsleep events. The mean point-biserial correlation between FD and the mean human rating was -0.213 indicating modest agreement. Cross-validated detection performance of the FD was poor with a mean correlation (phi = -0.099). This suggests that, on its own, FD of the EEG is unlikely to be useful for detecting microsleeps